Driving desired futures : turning design thinking into real innovation - Shamiyeh, Michael (Birkhaüser, 2014)
Driving Desired Futures addresses the question how do individuals in social systems achieve credibility for new ideas? What are the criteria that render the comprehension of new ideas more likely within a group of people with diverse sets of beliefs? What triggers management's attention to allocate resources to the development of new ideas? To address these questions, various authors discuss the structures and dynamics of developing new ideas.